Bibliometrics and altmetrics in the context of traditional, complementary, and integrative medicine - Jeremy Y. Ng; Dimity Stephen; Jianping Liu; Thomas Ostermann; Nicola Robinson; Holger Cramer (Integrative Medicine Research)
This educational article explores the utility of bibliometrics and altmetrics in evaluating traditional, complementary, and integrative medicine (TCIM) research. We introduce the concept of bibliometrics and altmetrics, provide an overview of the opportunities and challenges in using these analytical techniques, and highlight their future potential in TCIM research. Bibliometrics, based on publication and citation information, offer insights into TCIM research activity, output, scholarly influence, field structure, and collaboration practices. Altmetrics, including social media mentions, downloads, and online bookmarks, can capture the broader societal engagement with TCIM research beyond traditional academic circles. We discuss challenges and opportunities in utilizing these metrics effectively, such as addressing biases, incorporating cultural nuances, and exploring emerging trends. Additionally, we issue a call to action for researchers, policymakers, and practitioners to collaborate and leverage bibliometric and altmetric data to advance evidence-based healthcare practices to promote integrative approaches to health and wellness. By embracing a multidimensional approach to research evaluation, stakeholders can harness the potential of bibliometrics and altmetrics to improve TCIM research and healthcare delivery worldwide.